Crystalline silicon solar cell with high conversion efficiency and preparation process thereof

By using camellia petal templates to prepare bionic micro-nano composite films, depositing CuS nanocrystals/quantum dots on its surface, and adding phosphorus-doped graphene-doped glass powder to the positive electrode conductive paste, the problem of low photo absorption efficiency and carrier collection efficiency of crystalline silicon solar cells is solved, and the photoelectric conversion efficiency of solar cells is significantly improved.

CN119521832APending Publication Date: 2025-02-25NINGBO OSDA SOLAR CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411634229.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing crystalline silicon solar cells have low light absorption efficiency, low carrier collection efficiency, and large surface reflection loss in the short-wavelength spectrum, resulting in limited conversion efficiency.

Method used

Bionic micro-nano composite films were prepared using camellia petals as the original template, and CuS nanocrystals/quantum dots were deposited on its surface. At the same time, phosphorus-doped graphene-doped glass powder was added to the positive electrode conductive paste to improve the light absorption efficiency and carrier collection efficiency and reduce reflection loss.

Benefits of technology

By reducing the reflection loss of light at the interface, extending the propagation path of light, and increasing the absorption opportunity of light, the photoelectric conversion efficiency of solar cells is improved, and high open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119521832A_ABST
    Figure CN119521832A_ABST
Patent Text Reader

Abstract

The invention provides a crystalline silicon solar cell with high conversion efficiency and a preparation process thereof, and belongs to the technical field of solar cell preparation. The preparation process comprises the following steps: pretreating a crystal silicon wafer; preparing a bionic micro-nano composite film; preparing a composite structure on the surface of the silicon wafer; preparing the glass powder doped with the phosphorus-doped graphene; preparing a positive electrode conductive slurry; and preparing the crystalline silicon solar cell. The CuS nanocrystals / quantum dots are deposited on the surface of the bionic micro-nano composite film, the effects of antireflection, passivation and sensitization of the silicon wafer can be achieved, the photoelectric conversion efficiency of the battery is further improved, the CuS nanocrystals / quantum dots are deposited, the absorption range of the silicon wafer to the optical wavelength can be increased, and the photoelectric conversion efficiency of the battery is improved. Meanwhile, one absorbed photon can be converted into a plurality of photon-generated carriers through the CuS quantum effect, and the photoelectric conversion efficiency of the cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cell preparation, and in particular to a crystalline silicon solar cell with high conversion efficiency and a preparation process thereof. Background Art

[0002] As the global demand for clean energy grows, solar cells, as an important renewable energy conversion device, have received extensive attention and development. Crystalline silicon solar cells have become one of the mainstream solar cell types on the market due to their high conversion efficiency and stable performance. At present, crystalline silicon solar cells mainly include monocrystalline silicon solar cells and polycrystalline silicon solar cells.

[0003] Although crystalline silicon solar cells have made significant progress, there are still some problems in practical applications, mainly including:

[0004] Light absorption efficiency: Existing crystalline silicon solar cells have low light absorption efficiency in the short-wavelength spectral region, resulting in limited conversion efficiency.

[0005] Carrier collection efficiency: There is a large loss of carriers during the migration process inside the silicon wafer, which reduces the overall efficiency of the battery.

[0006] Surface reflection: Reflection loss on the cell surface is also an important factor, affecting the total light absorption of the cell.

[0007] Therefore, we propose a crystalline silicon solar cell with high conversion efficiency and its preparation process. Summary of the invention

[0008] In view of the deficiencies in the prior art, an object of the present invention is to provide a crystalline silicon solar cell with high conversion efficiency and a preparation process thereof.

[0009] A process for preparing a crystalline silicon solar cell with high conversion efficiency comprises the following steps:

[0010] S1: Pretreatment of crystalline silicon wafers

[0011] The silicon wafer after texturing is cleaned, the rinsed silicon wafer is corroded in a hydrofluoric acid solution and then in an ammonium fluoride solution, and then cleaned and dried to obtain a pre-treated silicon wafer;

[0012] S2: Preparation of biomimetic micro-nano composite films

[0013] Camellia petals were used as the original template, and a biomimetic polydimethylsiloxane film was prepared from a polydimethylsiloxane solution. Then, a copper oxide solution was spin-coated on the biomimetic polydimethylsiloxane film for hydrothermal growth to obtain a biomimetic micro-nano composite film.

[0014] S3: Preparation of composite structures on silicon wafer surfaces

[0015] The bionic micro-nano composite film is attached to the pre-treated silicon wafer, and then CuS is deposited on the bionic micro-nano composite film to obtain a silicon wafer based on CuS deposited on the bionic micro-nano composite film;

[0016] S4: Preparation of glass powder doped with phosphorus-doped graphene

[0017] Firstly, glass powder is prepared, then phosphorus-doped graphene is prepared, and the prepared phosphorus-doped graphene is doped into the glass powder to obtain glass powder doped with phosphorus-doped graphene;

[0018] S5: Preparation of positive electrode conductive slurry

[0019] The positive electrode conductive paste is prepared by mixing silver powder, phosphorus-doped graphene-doped glass powder and an organic carrier through a three-roll mixer;

[0020] S6: Preparation of crystalline silicon solar cells

[0021] The back electrode and aluminum back field are printed on the back of a silicon wafer with CuS deposited on a bionic micro-nano composite film, and the positive electrode conductive paste is printed on the front, which is then sintered to form a crystalline silicon solar cell.

[0022] Furthermore, step S1 of pre-processing the crystalline silicon wafer specifically includes the following steps:

[0023] S1.1: Mix 3-4 parts by weight of deionized water, 1-2 parts by weight of ammonia water and 1-2 parts by weight of hydrogen peroxide to obtain a cleaning solution, put the silicon wafer after texturing into the cleaning solution, and clean it at 50-60°C for 20-30 minutes, and rinse the cleaned silicon wafer again with distilled water for 2-3 times to obtain a rinsed silicon wafer;

[0024] S1.2: Place the rinsed silicon wafer into 50-60 parts by weight of 5-6wt% hydrofluoric acid solution, and ultrasonically corrode it for 2-3 minutes. Place the corroded silicon wafer again into 5-6mol / L ammonium fluoride solution, and ultrasonically treat it for 5-8 minutes. Then, rinse the silicon wafer with distilled water for 2-3 times, and put it into an oven to dry after rinsing to obtain the pretreated silicon wafer.

[0025] Furthermore, step S2 of preparing the bionic micro-nano composite film specifically comprises the following steps:

[0026] S2.1: Mix 2-3 parts by weight of a polydimethylsiloxane solution with 0.2-0.3 parts by weight of a DC184 silicone elastomer curing agent solution, and stir evenly to obtain a polydimethylsiloxane solution containing a curing agent;

[0027] S2.2: Cut clean camellia petals and place them on the cleaned ITO substrate, fix them with tape, add 1-2 parts by weight of polydimethylsiloxane solution containing a curing agent, let them stand for 20-30 minutes, put them in a vacuum oven, and cure them at 50-60°C for 5-6 hours. After peeling off the cured film, rinse them with ethanol and purified water for 2-3 times in turn to obtain a biomimetic polydimethylsiloxane film;

[0028] S2.3: adding hexamethylenetetramine in the same molar ratio to 0.1-0.2 parts by weight of a copper nitrate solution having a molar concentration of 0.02-0.05 mol / L, and mixing well to obtain a mixed solution;

[0029] S2.4: Spin coat 0.1-0.2 parts by weight of a 10-12 mg / mL copper oxide solution on a bionic polydimethylsiloxane film at a speed of 1000-1200 r / min, heat at 150-160°C for 60-70 min, cool and place in a mixed solution, hydrothermally grow at 70-75°C for 15-20 min, after the reaction is completed, take out the film, rinse with deionized water and anhydrous ethanol for 10-15 s, and dry at room temperature for 30-40 min to obtain a bionic micro-nano composite film.

[0030] Furthermore, step S3 of preparing the composite structure on the surface of the silicon wafer specifically includes the following steps:

[0031] S3.1: attaching the bionic micro-nano composite film to the pretreated silicon wafer, and hot pressing at 50-60°C and 3-5MPa for 10-20min to obtain a silicon wafer substrate;

[0032] S3.2: Immerse the silicon wafer substrate into 0.1-0.2mol / L copper acetate solution for 2-3min, take it out and dry it, immerse the dried silicon wafer substrate into 0.1-0.2mol / L thioacetamide for 2-3min, take it out and dry it, repeat the above operation 2-3 times, finally rinse it with ultrapure water, put it into an oven and dry it at 80-90℃ to obtain a silicon wafer with CuS deposited on the bionic micro-nano composite film.

[0033] Furthermore, step S4 of preparing the phosphorus-doped graphene-doped glass powder specifically comprises the following steps:

[0034] S4.1: Weigh 38.5-40 parts by weight of lead monoxide, 32-33 parts by weight of tellurium dioxide, 13-14 parts by weight of silicon dioxide, 4-5 parts by weight of thallium trioxide and 2-3 parts by weight of cesium oxide, put them in a mortar and grind them for 10-12 hours, put the ground powder into a crucible, transfer it to a box furnace and calcine it at 1100-1200°C for 30-40 minutes, pour it into distilled water after calcination, then wash it with anhydrous ethanol and distilled water for 2-3 times, and then dry and crush it to obtain glass powder with a particle size of 1-3μm;

[0035] S4.2: 15-18 parts by weight of graphene oxide are placed in a beaker, 0.1-0.2 parts by weight of phosphoric acid are added, and then 150-200 parts by weight of deionized water are added. After ultrasonic mixing, the solution is placed in a glass watch glass, and after vacuum freeze drying, it is placed in a quartz boat and quickly placed in a quartz tube in a tube furnace. After nitrogen is introduced, the tube furnace is heated to 800-900°C at a rate of 5-6°C / min, and then kept warm for 2-3 hours to obtain phosphorus-doped graphene;

[0036] S4.3: Add 0.2-0.3 parts by weight of phosphorus-doped graphene and 10-20 parts by weight of glass powder to 60-70 parts by weight of deionized water, ultrasonically disperse for 20-30 minutes, then add 10-12 parts by weight of ethylene glycol to obtain a mixed solution, add the mixed solution to an autoclave at 250-260°C, maintain the reaction rate at 15-20 r / min, react for 5-6 hours, wash and dry the reaction product to obtain phosphorus-doped graphene-doped glass powder.

[0037] Furthermore, step S5 of preparing the positive electrode conductive slurry specifically includes the following steps:

[0038] S5.1: Weigh 50-60 parts by weight of propylene glycol methyl ether acetate, 20-30 parts by weight of butyl carbitol acetate, 3-5 parts by weight of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 15-20 parts by weight of dibutyl phthalate into a beaker to obtain a mixed organic solvent;

[0039] S5.2: Stir the beaker containing the mixed organic solvent at a constant temperature of 25-26°C in a magnetic stirrer for 5-8 minutes, slowly add 5.5-6 parts by weight of polyisobutylene, raise the temperature to 50-60°C while stirring, then slowly add 4-5 parts by weight of thickener, stir at a constant temperature for 120-130 minutes, then add 1.5-2 parts by weight of thixotropic agent, maintain the temperature at 50-60°C, stir for 30-40 minutes, then take out and seal, and let stand at room temperature for 1-2 hours to obtain an organic carrier;

[0040] S5.3: 85-86 parts by weight of silver powder, 5-6 parts by weight of phosphorus-doped graphene-doped glass powder and 10-12 parts by weight of organic carrier are mixed by a three-roll mixer to prepare a positive electrode conductive paste.

[0041] Furthermore, step S6 of preparing the crystalline silicon solar cell specifically comprises the following steps:

[0042] S6.1: Printing back electrode and aluminum back field on the back of silicon wafer with CuS deposited on biomimetic micro-nano composite film;

[0043] S6.2: Printing a positive electrode conductive paste on the front side of a silicon wafer on which CuS is deposited on the biomimetic micro-nano composite film to form a positive electrode;

[0044] S6.3: Sintering the silicon wafer with CuS deposited on the bionic micro-nano composite film to form a crystalline silicon solar cell.

[0045] Furthermore, in step S5.2, the thixotropic agent is a mixture of hydrogenated castor oil and polyamide wax in a ratio of 1:1 by weight.

[0046] Furthermore, in step S5.2, the thickener is a mixture of ethyl cellulose EC50 and ethyl cellulose EC200 in a ratio of 1:1 by weight.

[0047] A crystalline silicon solar cell with high conversion efficiency is prepared by any of the above-mentioned processes for preparing a crystalline silicon solar cell with high conversion efficiency.

[0048] Compared with the prior art, the present invention has at least the following beneficial effects:

[0049] 1. The present invention prepares a bionic micro-nano composite film by using camellia petals as the original template. The hierarchical structure of the epidermal cells of the petals gives it broadband and omnidirectional optical properties, which can not only reduce optical losses but also redirect incident light. The camellia petals are mainly composed of raised cells on the surface of the petals. The micron-scale epidermal folds on the raised cells form a second-level hierarchical structure. Therefore, the surface of the prepared bionic micro-nano composite film has complex micro-nano structures, which can reduce the reflection loss of light at the interface. The hierarchical structure of the bionic micro-nano composite film gives the film broadband absorption characteristics, which can absorb light of different wavelengths and improve the utilization rate of light. At the same time, the hierarchical structure can redirect light incident at different angles, so that the light can be refracted and scattered multiple times inside the film, which not only extends the length of the light propagation path inside the material, but also makes the light stay longer inside the film, increasing the chance of light absorption. By reducing reflection losses, extending the light propagation path, and increasing the probability of light absorption, more light energy can be effectively utilized, thereby improving the conversion efficiency.

[0050] 2. The present invention deposits CuS nanocrystals / quantum dots on the surface of the bionic micro-nano composite film, which can achieve the effects of anti-reflection, passivation and sensitization of silicon wafers, thereby improving the photoelectric conversion efficiency of the battery. The deposition of CuS nanocrystals / quantum dots can increase the absorption range of the silicon wafer to the wavelength of light. At the same time, the CuS quantum effect can convert an absorbed photon into multiple photogenerated carriers, thereby improving the photoelectric conversion efficiency of the battery. The CuS nanocrystals / quantum dots and the CuO nanorod array can form a type II heterostructure, which can form a new PN heterojunction on the silicon surface, effectively enhancing the separation of electron-hole pairs in the silicon battery, increasing the collection of minority carriers, and thus enhancing the photoelectric conversion efficiency of the battery.

[0051] 3. The present invention prepares glass powder doped with phosphorus-doped graphene and adds it to the conductive paste of the positive electrode. The glass powder doped with phosphorus-doped graphene makes the average particle size of the glass small and uniform, increases the concentration of Ag particles at the interface of the glass layer, and greatly reduces the loss rate of the battery cell. The phosphorus-doped graphene fills the gap between the glass powder and the silver powder, so that the silver paste forms a good contact with the silicon base, thereby reducing the contact resistance, and the phosphorus atoms diffuse under the electrode, and the concentration of the n+ emitter increases. Both promote the rapid migration of electrons to the positive silver grid line, thereby improving the electrical performance of the battery. Due to the doping of phosphorus-doped graphene, when the glass enters the PN junction, the wide sintering window prevents the possible formation of PN junction puncture, thereby greatly reducing the possibility of low-efficiency batteries. Phosphorus-doped graphene to form an n-type emitter and optimize the PN junction will generate more carriers to increase the current output, so that the crystalline silicon solar cell produced by it has a higher open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency.

[0052] 4. The present invention pre-treats the silicon wafer, and after the pre-treatment, a silicon nanoparticle layer is formed on the surface of the silicon wafer. Since a Si-H structure is formed on the surface of the silicon wafer, this hydrogen-terminated structure makes the surface of the silicon wafer more stable. In addition, by treating the surface of the silicon wafer with hydrofluoric acid and ammonium fluoride, hydroxyl groups can be formed on the surface of the silicon wafer, which can react with siloxane in the bionic micro-nano composite film to enhance the binding force between the two, so that the bionic micro-nano composite film can be tightly combined with the silicon wafer. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0054] Figure 1 A flow chart of a process for preparing a crystalline silicon solar cell with high conversion efficiency adopted in an embodiment of the present invention. DETAILED DESCRIPTION

[0055] The following is a detailed description of a preparation process of a crystalline silicon solar cell with high conversion efficiency provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0056] Example 1

[0057] A process for preparing a crystalline silicon solar cell with high conversion efficiency, such as Figure 1 As shown, the following steps are included:

[0058] S1: Pretreatment of crystalline silicon wafers

[0059] S1.1: 3 parts by weight of deionized water, 1 part by weight of ammonia water and 1 part by weight of hydrogen peroxide are mixed to obtain a cleaning solution, the silicon wafer after texturing is placed in the cleaning solution, and cleaned at 50°C for 20 minutes, and the cleaned silicon wafer is rinsed again with distilled water twice to obtain a rinsed silicon wafer;

[0060] S1.2: Place the rinsed silicon wafer in 50 parts by weight of a 5wt% hydrofluoric acid solution and ultrasonically etch it for 2 minutes. Place the etched silicon wafer again in a 5mol / L ammonium fluoride solution and ultrasonically treat it for 5 minutes. Then, rinse the silicon wafer twice with distilled water and dry it in an oven to obtain a pretreated silicon wafer.

[0061] The texturing process includes placing the silicon wafer in a texturing tank, in a sodium hydroxide solution with a concentration of 15% and a temperature of 80°C, to form a velvet structure on the surface, thereby obtaining a silicon wafer after texturing;

[0062] S2: Preparation of biomimetic micro-nano composite films

[0063] S2.1: 2 parts by weight of a polydimethylsiloxane solution and 0.2 parts by weight of a DC184 silicone elastomer curing agent solution are mixed and stirred to obtain a polydimethylsiloxane solution containing a curing agent;

[0064] S2.2: Cut clean camellia petals and place them on the cleaned ITO substrate, fix them with tape, add 1 part by weight of polydimethylsiloxane solution containing a curing agent, let them stand for 20 minutes, put them in a vacuum oven, and cure them at 50°C for 5 hours. After peeling off the cured film, rinse them with ethanol and pure water twice in sequence to obtain a biomimetic polydimethylsiloxane film;

[0065] S2.3: Add hexamethylenetetramine in the same molar ratio to 0.1 parts by weight of a copper nitrate solution having a molar concentration of 0.02 mol / L, and mix well to obtain a mixed solution;

[0066] S2.4: Spin-coat 0.1 parts by weight of a 10 mg / mL copper oxide solution on the biomimetic polydimethylsiloxane film at a speed of 1000 r / min, and heat at 150°C for 60 min. After cooling, put it into the mixed solution and hydrothermally grow it at 70°C for 15 min. After the reaction is completed, take out the film, rinse it with deionized water and anhydrous ethanol for 10 s, and dry it at room temperature for 30 min to obtain the biomimetic micro-nano composite film.

[0067] S3: Preparation of composite structures on silicon wafer surfaces

[0068] S3.1: attaching the bionic micro-nano composite film to the pretreated silicon wafer, and hot pressing at 50°C and 3MPa for 10min to obtain a silicon wafer substrate;

[0069] S3.2: Immerse the silicon wafer substrate in a 0.1 mol / L copper acetate solution for 2 min, take it out and dry it, immerse the dried silicon wafer substrate in 0.1 mol / L thioacetamide for 2 min, take it out and dry it, repeat the above operation twice, finally rinse it with ultrapure water, put it in an oven and dry it at 80°C to obtain a silicon wafer with CuS deposited on the bionic micro-nano composite film;

[0070] S4: Preparation of glass powder doped with phosphorus-doped graphene

[0071] S4.1: Weigh 38.5 parts by weight of lead monoxide, 32 parts by weight of tellurium dioxide, 13 parts by weight of silicon dioxide, 4 parts by weight of thallium trioxide and 2 parts by weight of cesium oxide, put them in a mortar and grind them for 10 hours, put the ground powder into a crucible, transfer it to a box furnace and calcine it at 1100°C for 30 minutes, pour it into distilled water after calcination, then wash it twice with anhydrous ethanol and distilled water in turn, and then dry and crush it to obtain a glass powder with a particle size of 1 μm;

[0072] S4.2: 15 parts by weight of graphene oxide are placed in a beaker, 0.1 parts by weight of phosphoric acid is added, and then 150 parts by weight of deionized water are added. After ultrasonic mixing, the solution is placed in a glass watch glass, and after vacuum freeze drying, it is placed in a quartz boat and quickly placed in a quartz tube in a tube furnace. After nitrogen is introduced, the tube furnace is heated to 800°C at a rate of 5°C / min, and then kept warm for 2 hours to obtain phosphorus-doped graphene;

[0073] S4.3: adding 0.2 parts by weight of phosphorus-doped graphene and 10 parts by weight of glass powder to 60 parts by weight of deionized water, and ultrasonically dispersing for 20 minutes, and then adding 10 parts by weight of ethylene glycol to obtain a mixed solution, adding the mixed solution to an autoclave at 250° C., maintaining the reaction rate at 15 r / min, and reacting for 5 hours, and washing and drying the reaction product to obtain phosphorus-doped graphene-doped glass powder;

[0074] S5: Preparation of positive electrode conductive slurry

[0075] S5.1: Weigh 50 parts by weight of propylene glycol methyl ether acetate, 20 parts by weight of butyl carbitol acetate, 3 parts by weight of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 15 parts by weight of dibutyl phthalate into a beaker to obtain a mixed organic solvent;

[0076] S5.2: Stir the beaker containing the mixed organic solvent at a constant temperature of 25°C in a magnetic stirrer for 5 minutes, slowly add 5.5 parts by weight of polyisobutylene, raise the temperature to 50°C while stirring, then slowly add 4 parts by weight of thickener, stir at a constant temperature for 120 minutes, then add 1.5 parts by weight of thixotropic agent, maintain the temperature at 50°C, stir for 30 minutes, take out and seal, and let stand at room temperature for 1 hour to obtain an organic carrier;

[0077] S5.3: 85 parts by weight of silver powder, 5 parts by weight of phosphorus-doped graphene-doped glass powder and 10 parts by weight of an organic carrier are mixed by a three-roll mixer to prepare a positive electrode conductive paste;

[0078] Thixotropic agent: a mixture of hydrogenated castor oil and polyamide wax in a ratio of 1:1 by weight;

[0079] Thickener: ethyl cellulose EC50 and ethyl cellulose EC200 mixed in a ratio of 1:1 by weight;

[0080] S6: Preparation of crystalline silicon solar cells

[0081] S6.1: Printing back electrode and aluminum back field on the back of silicon wafer with CuS deposited on biomimetic micro-nano composite film;

[0082] S6.2: Printing a positive electrode conductive paste on the front side of a silicon wafer on which CuS is deposited on the biomimetic micro-nano composite film to form a positive electrode;

[0083] S6.3: Sintering the silicon wafer with CuS deposited on the bionic micro-nano composite film to form a crystalline silicon solar cell.

[0084] Example 2

[0085] A process for preparing a crystalline silicon solar cell with high conversion efficiency, such as Figure 1 As shown, the following steps are included:

[0086] S1: Pretreatment of crystalline silicon wafers

[0087] S1.1: 4 parts by weight of deionized water, 2 parts by weight of ammonia water and 2 parts by weight of hydrogen peroxide are mixed to obtain a cleaning solution, the silicon wafer after texturing is placed in the cleaning solution, and cleaned at 50°C for 20 minutes, and the cleaned silicon wafer is rinsed again with distilled water twice to obtain a rinsed silicon wafer;

[0088] S1.2: The rinsed silicon wafer is placed in 60 parts by weight of a 6wt% hydrofluoric acid solution and subjected to ultrasonic etching for 2 minutes. The etched silicon wafer is placed in a 6mol / L ammonium fluoride solution again and subjected to ultrasonic treatment for 5 minutes. The silicon wafer is then rinsed twice with distilled water and dried in an oven to obtain a pretreated silicon wafer.

[0089] The texturing process includes placing the silicon wafer in a texturing tank, in a 20% sodium hydroxide solution at a temperature of 80°C, to organize the surface to form a velvet structure, and obtain a silicon wafer after texturing;

[0090] S2: Preparation of biomimetic micro-nano composite films

[0091] S2.1: 3 parts by weight of a polydimethylsiloxane solution and 0.3 parts by weight of a DC184 silicone elastomer curing agent solution are mixed and stirred to obtain a polydimethylsiloxane solution containing a curing agent;

[0092] S2.2: Cut clean camellia petals and place them on the cleaned ITO substrate, fix them with tape, add 2 parts by weight of polydimethylsiloxane solution containing a curing agent, let them stand for 20 minutes, put them in a vacuum oven, and cure them at 50°C for 5 hours. After peeling off the cured film, rinse them with ethanol and pure water twice in sequence to obtain a biomimetic polydimethylsiloxane film;

[0093] S2.3: Add hexamethylenetetramine in the same molar ratio to 0.2 parts by weight of a copper nitrate solution having a molar concentration of 0.05 mol / L, and mix well to obtain a mixed solution;

[0094] S2.4: Spin-coat 0.2 parts by weight of a 12 mg / mL copper oxide solution on the biomimetic polydimethylsiloxane film at a speed of 1000 r / min, heat at 150°C for 60 min, cool and put into the mixed solution, hydrothermally grow at 70°C for 15 min, take out the film after the reaction, rinse with deionized water and anhydrous ethanol for 10 s, and dry at room temperature for 30 min to obtain the biomimetic micro-nano composite film;

[0095] S3: Preparation of composite structures on silicon wafer surfaces

[0096] S3.1: attaching the bionic micro-nano composite film to the pretreated silicon wafer, and hot pressing at 50°C and 3MPa for 10min to obtain a silicon wafer substrate;

[0097] S3.2: Immerse the silicon wafer substrate in a 0.2 mol / L copper acetate solution for 2 min, take it out and dry it, immerse the dried silicon wafer substrate in a 0.2 mol / L thioacetamide for 2 min, take it out and dry it, repeat the above operation twice, finally rinse it with ultrapure water, put it in an oven and dry it at 80°C to obtain a silicon wafer with CuS deposited on a bionic micro-nano composite film;

[0098] S4: Preparation of glass powder doped with phosphorus-doped graphene

[0099] S4.1: Weigh 40 parts by weight of lead monoxide, 33 parts by weight of tellurium dioxide, 14 parts by weight of silicon dioxide, 5 parts by weight of thallium trioxide and 3 parts by weight of cesium oxide, put them in a mortar and grind them for 10 hours, put the ground powder into a crucible, transfer it to a box furnace and calcine it at 1100°C for 30 minutes, pour it into distilled water after calcination, then wash it twice with anhydrous ethanol and distilled water in turn, and then dry and crush it to obtain a glass powder with a particle size of 1 μm;

[0100] S4.2: 18 parts by weight of graphene oxide are placed in a beaker, 0.2 parts by weight of phosphoric acid is added, and then 200 parts by weight of deionized water are added. After ultrasonic mixing, the solution is placed in a glass watch glass, and after vacuum freeze drying, it is placed in a quartz boat and quickly placed in a quartz tube in a tube furnace. After nitrogen is introduced, the tube furnace is heated to 800°C at a rate of 5°C / min, and then kept warm for 2 hours to obtain phosphorus-doped graphene;

[0101] S4.3: 0.3 parts by weight of phosphorus-doped graphene and 20 parts by weight of glass powder are added to 70 parts by weight of deionized water, and ultrasonically dispersed for 20 minutes, and then 12 parts by weight of ethylene glycol are added to obtain a mixed solution, and the mixed solution is added to an autoclave at 250° C., and the reaction rate is maintained at 15 r / min, and the reaction is carried out for 5 hours. The reaction product is washed and dried to obtain phosphorus-doped graphene-doped glass powder;

[0102] S5: Preparation of positive electrode conductive slurry

[0103] S5.1: Weigh 60 parts by weight of propylene glycol methyl ether acetate, 30 parts by weight of butyl carbitol acetate, 5 parts by weight of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 20 parts by weight of dibutyl phthalate into a beaker to obtain a mixed organic solvent;

[0104] S5.2: Stir the beaker containing the mixed organic solvent at a constant temperature of 25°C for 5 minutes in a magnetic stirrer, slowly add 6 parts by weight of polyisobutylene, raise the temperature to 50°C while stirring, then slowly add 5 parts by weight of thickener, stir at a constant temperature for 120 minutes, then add 2 parts by weight of thixotropic agent, maintain the temperature at 50°C, stir for 30 minutes, take out and seal, and let stand at room temperature for 1 hour to obtain an organic carrier;

[0105] S5.3: 86 parts by weight of silver powder, 6 parts by weight of phosphorus-doped graphene-doped glass powder and 12 parts by weight of an organic carrier are mixed by a three-roll mixer to prepare a positive electrode conductive paste;

[0106] Thixotropic agent: a mixture of hydrogenated castor oil and polyamide wax in a ratio of 1:1 by weight;

[0107] Thickener: ethyl cellulose EC50 and ethyl cellulose EC200 mixed in a ratio of 1:1 by weight;

[0108] S6: Preparation of crystalline silicon solar cells

[0109] S6.1: Printing back electrode and aluminum back field on the back of silicon wafer with CuS deposited on biomimetic micro-nano composite film;

[0110] S6.2: Printing a positive electrode conductive paste on the front side of a silicon wafer on which CuS is deposited on the biomimetic micro-nano composite film to form a positive electrode;

[0111] S6.3: Sintering the silicon wafer with CuS deposited on the bionic micro-nano composite film to form a crystalline silicon solar cell.

[0112] Example 3

[0113] A process for preparing a crystalline silicon solar cell with high conversion efficiency, such as Figure 1 As shown, the following steps are included:

[0114] S1: Pretreatment of crystalline silicon wafers

[0115] S1.1: Mix 3 parts by weight of deionized water, 1 part by weight of ammonia water and 1 part by weight of hydrogen peroxide to obtain a cleaning solution, put the silicon wafer after texturing into the cleaning solution, and clean it at 60°C for 30 minutes, and rinse the cleaned silicon wafer again with distilled water for 3 times to obtain a rinsed silicon wafer;

[0116] S1.2: Place the rinsed silicon wafer in 50 parts by weight of a 5wt% hydrofluoric acid solution and ultrasonically etch it for 3 minutes. Place the etched silicon wafer again in a 5mol / L ammonium fluoride solution and ultrasonically treat it for 8 minutes. Then, rinse the silicon wafer with distilled water for 3 times and dry it in an oven to obtain a pretreated silicon wafer.

[0117] The texturing process includes placing the silicon wafer in a texturing tank, in a sodium hydroxide solution with a concentration of 15% and a temperature of 85°C, to form a velvet structure on the surface, thereby obtaining a silicon wafer after texturing;

[0118] S2: Preparation of biomimetic micro-nano composite films

[0119] S2.1: 2 parts by weight of a polydimethylsiloxane solution and 0.2 parts by weight of a DC184 silicone elastomer curing agent solution are mixed and stirred to obtain a polydimethylsiloxane solution containing a curing agent;

[0120] S2.2: Cut clean camellia petals and place them on the cleaned ITO substrate, fix them with tape, add 1 part by weight of polydimethylsiloxane solution containing a curing agent, let them stand for 30 minutes, put them in a vacuum oven, and cure them at 60°C for 6 hours. After peeling off the cured film, rinse them with ethanol and pure water three times in sequence to obtain a biomimetic polydimethylsiloxane film;

[0121] S2.3: Add hexamethylenetetramine in the same molar ratio to 0.1 parts by weight of a copper nitrate solution having a molar concentration of 0.02 mol / L, and mix well to obtain a mixed solution;

[0122] S2.4: Spin-coat 0.1 parts by weight of a 10 mg / mL copper oxide solution on a biomimetic polydimethylsiloxane film at a speed of 1000 r / min, heat at 160°C for 70 min, cool and place in a mixed solution, hydrothermally grow at 75°C for 20 min, take out the film after the reaction, rinse with deionized water and anhydrous ethanol for 15 s, and dry at room temperature for 40 min to obtain a biomimetic micro-nano composite film;

[0123] S3: Preparation of composite structures on silicon wafer surfaces

[0124] S3.1: attaching the bionic micro-nano composite film to the pretreated silicon wafer, and hot pressing at 60°C and 5MPa for 20min to obtain a silicon wafer substrate;

[0125] S3.2: Immerse the silicon wafer substrate in a 0.1 mol / L copper acetate solution for 3 min, take it out and dry it, immerse the dried silicon wafer substrate in a 0.1 mol / L thioacetamide for 3 min, take it out and dry it, repeat the above operation 3 times, finally rinse it with ultrapure water, put it in an oven and dry it at 90°C to obtain a silicon wafer with CuS deposited on a bionic micro-nano composite film;

[0126] S4: Preparation of glass powder doped with phosphorus-doped graphene

[0127] S4.1: Weigh 38.5 parts by weight of lead monoxide, 32 parts by weight of tellurium dioxide, 13 parts by weight of silicon dioxide, 4 parts by weight of thallium trioxide and 2 parts by weight of cesium oxide, put them in a mortar and grind them for 12 hours, put the ground powder into a crucible, transfer it to a box furnace and calcine it at 1200°C for 40 minutes, pour it into distilled water after calcination, then wash it with anhydrous ethanol and distilled water three times in sequence, and then dry and crush it to obtain a glass powder with a particle size of 3μm;

[0128] S4.2: 15 parts by weight of graphene oxide are placed in a beaker, 0.1 parts by weight of phosphoric acid is added, and then 150 parts by weight of deionized water are added. After ultrasonic mixing, the solution is placed in a glass watch glass, and after vacuum freeze drying, it is placed in a quartz boat and quickly placed in a quartz tube in a tube furnace. After nitrogen is introduced, the tube furnace is heated to 900°C at a rate of 6°C / min, and then kept warm for 3 hours to obtain phosphorus-doped graphene;

[0129] S4.3: adding 0.2 parts by weight of phosphorus-doped graphene and 10 parts by weight of glass powder to 60 parts by weight of deionized water, and ultrasonically dispersing for 30 minutes, and then adding 10 parts by weight of ethylene glycol to obtain a mixed solution, adding the mixed solution to an autoclave at 260° C., maintaining the reaction rate at 20 r / min, and reacting for 6 hours, and washing and drying the reaction product to obtain phosphorus-doped graphene-doped glass powder;

[0130] S5: Preparation of positive electrode conductive slurry

[0131] S5.1: Weigh 50 parts by weight of propylene glycol methyl ether acetate, 20 parts by weight of butyl carbitol acetate, 3 parts by weight of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 15 parts by weight of dibutyl phthalate into a beaker to obtain a mixed organic solvent;

[0132] S5.2: Stir the beaker containing the mixed organic solvent at a constant temperature of 26°C in a magnetic stirrer for 8 minutes, slowly add 5.5 parts by weight of polyisobutylene, raise the temperature to 60°C while stirring, then slowly add 4 parts by weight of thickener, stir at a constant temperature for 130 minutes, then add 1.5 parts by weight of thixotropic agent, maintain the temperature at 60°C, stir for 40 minutes, take out and seal, and let stand at room temperature for 2 hours to obtain an organic carrier;

[0133] S5.3: 85 parts by weight of silver powder, 5 parts by weight of phosphorus-doped graphene-doped glass powder and 10 parts by weight of an organic carrier are mixed by a three-roll mixer to prepare a positive electrode conductive paste;

[0134] Thixotropic agent: a mixture of hydrogenated castor oil and polyamide wax in a ratio of 1:1 by weight;

[0135] Thickener: ethyl cellulose EC50 and ethyl cellulose EC200 mixed in a ratio of 1:1 by weight;

[0136] S6: Preparation of crystalline silicon solar cells

[0137] S6.1: Printing back electrode and aluminum back field on the back of silicon wafer with CuS deposited on biomimetic micro-nano composite film;

[0138] S6.2: Printing a positive electrode conductive paste on the front side of a silicon wafer on which CuS is deposited on the biomimetic micro-nano composite film to form a positive electrode;

[0139] S6.3: Sintering the silicon wafer with CuS deposited on the bionic micro-nano composite film to form a crystalline silicon solar cell.

[0140] Comparative Example 1

[0141] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes step S3.2, replaces the silicon wafer based on CuS deposited on the bionic micro-nano composite film in step S6 with a silicon wafer substrate, and prepares a crystalline silicon solar cell without changing the other steps, which is recorded as Comparative Example 1.

[0142] Comparative Example 2

[0143] Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes step S3.1 and replaces step S2 with "evenly coating 20mmol / LCu(ac)2 ethanol solution on the surface of the pretreated silicon wafer, then placing the silicon wafer in an oven at 120°C to dry, repeating twice, and then annealing in an oven at 250°C for 10 hours to obtain a silicon wafer with a deposited seed layer, after washing it twice with deionized water, placing it in 0.1 weight parts of copper nitrate solution with a molar concentration of 0.02mol / L, adding hexamethylenetetramine in the same molar ratio, hydrothermally growing it at 70°C for 15min, then washing it with deionized water and drying it to obtain a silicon wafer substrate", and the other steps remain unchanged to prepare a crystalline silicon solar cell, which is recorded as Comparative Example 2.

[0144] Comparative Example 3

[0145] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes steps S4.2-4.3, replaces the phosphorus-doped graphene-doped glass powder in step S5.1 with an equal weight of glass powder, and prepares a crystalline silicon solar cell without changing the other steps, which is recorded as Comparative Example 3.

[0146] The open circuit voltage, short circuit current, fill factor and conversion efficiency of Examples 1-3 and Comparative Examples 1-3 were measured using a solar cell volt-ampere characteristic test system (model: SoliA, provided by Newport-Orie, USA). The measurement results are shown in Table 1.

[0147] Table 1. Performance tests of Examples 1-3 and Comparative Examples 1-3

[0148]

[0149] It can be seen from the data in Table 1 that the data of Comparative Example 1 is better than that of the embodiment, indicating that the photoelectric conversion efficiency of the battery is effectively improved by depositing CuS nanocrystals / quantum dots on the surface of the bionic micro-nano composite film; the data of Comparative Example 2 is also higher than that of the embodiment. It can be seen from the data of Comparative Examples 1 and 2 that the bionic micro-nano composite film prepared by using camellia petals as the original template can make more light energy be effectively utilized, thereby improving the conversion efficiency. At the same time, the synergistic effect of depositing CuS nanocrystals / quantum dots on the surface of the bionic micro-nano composite film can further improve the conversion efficiency; the various data of Comparative Example 3 are also higher than those of the embodiment, indicating that the crystalline silicon solar cell prepared by adding phosphorus-doped graphene-doped glass powder to the positive electrode conductive slurry has higher open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency.

[0150] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a crystalline silicon solar cell with high conversion efficiency, characterized in that: The steps include: S1: Pretreatment of crystalline silicon wafers The silicon wafer after texturing is cleaned, the rinsed silicon wafer is corroded in a hydrofluoric acid solution and then in an ammonium fluoride solution, and then cleaned and dried to obtain a pre-treated silicon wafer; S2: Preparation of biomimetic micro-nano composite films Camellia petals were used as the original template, and a biomimetic polydimethylsiloxane film was prepared from a polydimethylsiloxane solution. Then, a copper oxide solution was spin-coated on the biomimetic polydimethylsiloxane film for hydrothermal growth to obtain a biomimetic micro-nano composite film. S3: Preparation of composite structures on silicon wafer surfaces The bionic micro-nano composite film is attached to the pre-treated silicon wafer, and then CuS is deposited on the bionic micro-nano composite film to obtain a silicon wafer based on CuS deposited on the bionic micro-nano composite film; S4: Preparation of glass powder doped with phosphorus-doped graphene Firstly, glass powder is prepared, then phosphorus-doped graphene is prepared, and the prepared phosphorus-doped graphene is doped into the glass powder to obtain glass powder doped with phosphorus-doped graphene; S5: Preparation of positive electrode conductive slurry The positive electrode conductive paste is prepared by mixing silver powder, phosphorus-doped graphene-doped glass powder and an organic carrier through a three-roll mixer; S6: Preparation of crystalline silicon solar cells The back electrode and aluminum back field are printed on the back of a silicon wafer with CuS deposited on a bionic micro-nano composite film, and the positive electrode conductive paste is printed on the front, which is then sintered to form a crystalline silicon solar cell.

2. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 1, characterized in that: Step S1: Pretreatment of the crystalline silicon wafer, specifically comprising the following steps: S1.1: Mix 3-4 parts by weight of deionized water, 1-2 parts by weight of ammonia water and 1-2 parts by weight of hydrogen peroxide to obtain a cleaning solution, put the silicon wafer after texturing into the cleaning solution, and clean it at 50-60°C for 20-30 minutes, and rinse the cleaned silicon wafer again with distilled water for 2-3 times to obtain a rinsed silicon wafer; S1.2: Place the rinsed silicon wafer into 50-60 parts by weight of 5-6wt% hydrofluoric acid solution, and ultrasonically corrode it for 2-3 minutes. Place the corroded silicon wafer again into 5-6mol / L ammonium fluoride solution, and ultrasonically treat it for 5-8 minutes. Then, rinse the silicon wafer with distilled water for 2-3 times, and put it into an oven to dry after rinsing to obtain the pretreated silicon wafer.

3. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 2, characterized in that: Step S2: Preparation of biomimetic micro-nano composite film, specifically comprising the following steps: S2.1: Mix 2-3 parts by weight of polydimethylsiloxane solution and 0.2-0.3 parts by weight of DC184 silicone elastomer curing agent solution, and stir evenly to obtain a polydimethylsiloxane solution containing a curing agent. S2.2: Cut clean camellia petals and place them on the cleaned ITO substrate, fix them with tape, add 1-2 parts by weight of polydimethylsiloxane solution containing a curing agent, let them stand for 20-30 minutes, put them in a vacuum oven, and cure them at 50-60°C for 5-6 hours. After peeling off the cured film, rinse them with ethanol and purified water for 2-3 times in turn to obtain a biomimetic polydimethylsiloxane film; S2.3: adding hexamethylenetetramine in the same molar ratio to 0.1-0.2 parts by weight of a copper nitrate solution having a molar concentration of 0.02-0.05 mol / L, and mixing well to obtain a mixed solution; S2.4: Spin coat 0.1-0.2 parts by weight of a 10-12 mg / mL copper oxide solution on a bionic polydimethylsiloxane film at a speed of 1000-1200 r / min, heat at 150-160°C for 60-70 min, cool and place in a mixed solution, hydrothermally grow at 70-75°C for 15-20 min, after the reaction is completed, take out the film, rinse with deionized water and anhydrous ethanol for 10-15 s, and dry at room temperature for 30-40 min to obtain a bionic micro-nano composite film.

4. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 3, characterized in that: Step S3: Preparation of the composite structure on the surface of the silicon wafer, specifically comprising the following steps: S3.1: attaching the bionic micro-nano composite film to the pretreated silicon wafer, and hot pressing at 50-60°C and 3-5MPa for 10-20min to obtain a silicon wafer substrate; S3.2: Immerse the silicon wafer substrate into 0.1-0.2mol / L copper acetate solution for 2-3min, take it out and dry it, immerse the dried silicon wafer substrate into 0.1-0.2mol / L thioacetamide for 2-3min, take it out and dry it, repeat the above operation 2-3 times, finally rinse it with ultrapure water, put it into an oven and dry it at 80-90℃ to obtain a silicon wafer with CuS deposited on the bionic micro-nano composite film.

5. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 4, characterized in that: Step S4: Preparation of phosphorus-doped graphene-doped glass powder, specifically comprising the following steps: S4.1: Weigh 38.5-40 parts by weight of lead monoxide, 32-33 parts by weight of tellurium dioxide, 13-14 parts by weight of silicon dioxide, 4-5 parts by weight of thallium trioxide and 2-3 parts by weight of cesium oxide, put them in a mortar and grind them for 10-12 hours, put the ground powder into a crucible, transfer it to a box furnace and calcine it at 1100-1200°C for 30-40 minutes, pour it into distilled water after calcination, then wash it with anhydrous ethanol and distilled water for 2-3 times, and then dry and crush it to obtain glass powder with a particle size of 1-3μm; S4.2: 15-18 parts by weight of graphene oxide are placed in a beaker, 0.1-0.2 parts by weight of phosphoric acid are added, and then 150-200 parts by weight of deionized water are added. After ultrasonic mixing, the solution is placed in a glass watch glass, and after vacuum freeze drying, it is placed in a quartz boat and quickly placed in a quartz tube in a tube furnace. After nitrogen is introduced, the tube furnace is heated to 800-900°C at a rate of 5-6°C / min, and then kept warm for 2-3 hours to obtain phosphorus-doped graphene; S4.3: Add 0.2-0.3 parts by weight of phosphorus-doped graphene and 10-20 parts by weight of glass powder to 60-70 parts by weight of deionized water, ultrasonically disperse for 20-30 minutes, then add 10-12 parts by weight of ethylene glycol to obtain a mixed solution, add the mixed solution to an autoclave at 250-260°C, maintain the reaction rate at 15-20 r / min, react for 5-6 hours, wash and dry the reaction product to obtain phosphorus-doped graphene-doped glass powder.

6. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 5, characterized in that: Step S5: Preparation of positive electrode conductive slurry, specifically including the following steps: S5.1: Weigh 50-60 parts by weight of propylene glycol methyl ether acetate, 20-30 parts by weight of butyl carbitol acetate, 3-5 parts by weight of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 15-20 parts by weight of dibutyl phthalate into a beaker to obtain a mixed organic solvent; S5.2: Stir the beaker containing the mixed organic solvent in a magnetic stirrer at a constant temperature of 25-26°C for 5-8 minutes, slowly add 5.5-6 parts by weight of polyisobutylene, raise the temperature to 50-60°C while stirring, then slowly add 4-5 parts by weight of thickener, stir at a constant temperature for 120-130 minutes, then add 1.5-2 parts by weight of thixotropic agent, maintain the temperature at 50-60°C, stir for 30-40 minutes, then take out and seal, let stand at room temperature for 1-2 hours to obtain an organic carrier; S5.3: 85-86 parts by weight of silver powder, 5-6 parts by weight of phosphorus-doped graphene-doped glass powder and 10-12 parts by weight of organic carrier are mixed by a three-roll mixer to prepare a positive electrode conductive slurry.

7. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 6, characterized in that: Step S6: Preparation of crystalline silicon solar cells, specifically comprising the following steps: S6.1: Printing a back electrode and an aluminum back field on the back of a silicon wafer on which CuS is deposited on a biomimetic micro-nano composite film; S6.2: Printing a positive electrode conductive paste on the front of a silicon wafer on which CuS is deposited on a biomimetic micro-nano composite film to form a positive electrode; S6.3: Sintering the silicon wafer with CuS deposited on the bionic micro-nano composite film to form a crystalline silicon solar cell.

8. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 6, characterized in that: The thixotropic agent in step S5.2 is a mixture of hydrogenated castor oil and polyamide wax in a ratio of 1:1 by weight.

9. The process for preparing a crystalline silicon solar cell with high conversion efficiency according to claim 6, characterized in that: The thickener in step S5.2 is a mixture of ethyl cellulose EC50 and ethyl cellulose EC200 in a ratio of 1:1 by weight.

10. A crystalline silicon solar cell with high conversion efficiency, characterized in that: The crystalline silicon solar cell is prepared by the preparation process of a crystalline silicon solar cell with high conversion efficiency as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Conductive silver paste for photovoltaic cell and preparation method thereof

    CN120527058A